Crown Gall Disease Susceptibility of Some Stone Fruit Rootstocks in Turkey - Sümer Horuz; Mustafa Küsek; Behçet Kemal Çağlar; Yeşim Aysan (Journal of Agricultural Sciences)
Rhizobium radiobacter formerly known as Agrobacterium tumefaciens, is the most important bacterial pathogen causing crown gall disease on over 750 different plant species including ornamentals, vegetables and fruit trees. This pathogen causes crown galls on root and stems of plants and rarely on, above-soil parts of plants. Biological control is successfully used in disease management; however, such strategies are quite ineffective in disease contaminated soils or seedlings. Thus, growers and scientists are mostly focused on disease resistant cultivars or rootstocks. In this study, crown gall disease reactions of three widely used rootstocks Garnem, Myrobolan and GF-677 for stone fruit trees were evaluated. A drop of bacterial suspension of 109 cfu mL-1 were inoculated onto three individual wounds over 90 shoots per rootstock. The weights and sizes of the tumor formed were measured five months after rootstock inoculations. The size of produced galls on rootstocks Garnem, Myrobolan and GF-677 were 0.16-5.28 mm, 0.09-4.42 mm and 0.09-0.36 mm, respectively. However, the weights of the galls varied between 0.02-2.85 g in Garnem, 0.01-1.58 g in Myrobolan and 0.02-0.11 g in GF-677 rootstocks. According to statistical analyses of gall formations, rootstocks were placed in different groups, additionally, none of them were found resistant to crown gall disease. Among the three rootstock tested, the study revealed that Garnem was highly susceptible, Myrobolan was moderately susceptible and GF-677 rootstock was less susceptible to crown gall disease. When an orchard will be intended to be newly planted with stone fruit trees, hence, GF-677 type rootstock would be a good choice to be preferred for planting in new orchards.